ANALISIS PERILAKU PEMILIH MASYARAKAT KOTA JAMBI DALAM MENENTUKAN CALON GUBERNUR PROVINSI JAMBI TAHUN 2024 - Dimas Rizal; Sutri Destemi Elsi (Mimbar : Jurnal Penelitian Sosial Dan Politik, 2024)
General elections (elections) are a means of implementing popular sovereignty, where the people determine for themselves the choices they believe in. This means that the people have full power to determine their leaders, because the people hold the highest power. Jambi Province is a socially plural region, there are several tribes in Jambi province including 44% of Jambi origin tribes, 29% of Javanese, followed by 5% Malays, 5% Minangkabau, 4% Batak, 3% Banjar. , Bugis 3%, Sundanese 3%, Tribes from South Sumatra 3%, Chinese 1%, and Others 1%. The approach taken in this research used a qualitative descriptive approach with purposive sampling techniques with interview techniques with direct informant sources. From the results of the research, voter behavior in Jambi City from an organizational and youth perspective can be taken broadly. The behavior of the people of Jambi City can be categorized as rational and critical voter behavior. This is supported by data that shows the demands and expectations they want from the candidates who will run in the 2024 election for governor of Jambi Province. The vision and mission and work programs they offer to the community will be the main factors for the people of Jambi city in making their choice. Political parties in the results of this research do not have a large role in determining society's choices.